2022
DOI: 10.3390/ijerph19137644
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Malay Version of the Childbirth Experience Questionnaire (CEQ-My)

Abstract: Negative childbirth experience may cause adverse psychological effects in postpartum mothers. The Childbirth Experience Questionnaire (CEQ) is a multidimensional tool designed to assess women’s perceptions of labour and birth. We aim to validate the Malay version of the CEQ (CEQ-My) and evaluate its psychometric properties. The previously published Malay-translated CEQ was reviewed by a panel of experts and underwent minor changes. The original visual analogue scoring (VAS) was changed to a numerical scale. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Similar to the study by Boie et al 24 , which validated the use of the CEQ in Denmark, we found a three-dimensional model slightly different from the original four-dimensional model shown in both studies by Dencker et al 19,25 and by other studies that have validated the CEQ [21][22][23] . Most items originally within the domain 'Perceived safety' (items 2, 18, 19, 15) were grouped with the 'Own capacity' domain in our model, and items related to feeling secure (items 17 and 22) were grouped with the domain 'Professional support'.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to the study by Boie et al 24 , which validated the use of the CEQ in Denmark, we found a three-dimensional model slightly different from the original four-dimensional model shown in both studies by Dencker et al 19,25 and by other studies that have validated the CEQ [21][22][23] . Most items originally within the domain 'Perceived safety' (items 2, 18, 19, 15) were grouped with the 'Own capacity' domain in our model, and items related to feeling secure (items 17 and 22) were grouped with the domain 'Professional support'.…”
Section: Discussionsupporting
confidence: 84%
“…Women who had operative births were known to score lower using the CEQ 21,24 . In the original study by Denkcer et al 19 , and in the studies by Kalok et al 23 and Boie et al 24 , women with operative birth scored lower in all domains 19,23,24 . We cannot compare their results directly with ours, as they included both emergency cesarean sections and operative vaginal births, and our study looks at emergency cesarean sections only.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This can also be seen in other studies, where this item obtained sufficient but lower factor loads than the rest [ 31 , 45 ]. Other studies report adequate factor load values for the item [ 34 , 36 , 64 , 65 ]. This finding could not be compared in all studies since either they did not conduct factor analysis [ 32 , 40 , 42 ] or did not report factor loads obtained for the items [ 30 , 33 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…has been discarded in other studies for this reason. Kalok A et al eliminated it from the Malay version due to a negative load (-0.822) [ 34 ]. In the studies of Zhu X et al (Chinese version) [ 31 ] and Lok KYK et al, it was also discarded [ 43 ].…”
Section: Discussionmentioning
confidence: 99%